DISTINGSI KEILMUAN SOSIOLOGI AGAMA (Sejarah Perkembangan, Epistemologi, dan Kontribusi Praksis) - Moh Soehadha (Jurnal Sosiologi Agama, 2018)
Sociology studies of religion today have developed in various Islamic colleges in Indonesia. As a science developed in universities, the sociology of religion is built with a strong epistemological foundation. Unlike the sociology of religion developed from sociology in public universities, the sociology of religion in Islamic higher education is also influenced by the Comparative Science of Religion or the Study of Religions. The following article describes the development of religious sociology studies at the UIN Sunan Kalijaga which is distinctive. The distinction of the study of the sociology of religion is influenced by the history of the development of religious sociology study programs and the praxis of religious sociology to solve social and religious problems in Indonesia. Studi sosiologi agama dewasa ini telah berkembang di berbagai perguruan tinggi agama Islam di Indonesia. Sebagai ilmu pengetahuan yang dikembangkan di perguruan tinggi,  maka sosiologi agama dibangun dengan landasan  epistemologi yang kuat. Berbeda dengan sosiologi agama yang dikembangkan dari ilmu sosiologi yang ada di perguruan tinggi umum, sosiologi agama di perguruan tinggi agama Islam juga dipengaruhi oleh Ilmu Perbandingan Agama atau Studi Agama-agama. Tulisan berikut mendeskripsikan tentang perkembangan studi sosiologi agama di UIN Sunan Kalijaga yang bersifat distingtif. Distingsi kajian sosiologi agama tersebut dipengaruhi oleh sejarah perkembangan program studi sosiologi agama dan kebutuhan praksis sosiologi agama untuk menyelesaikan problem sosial keagamaan di Indonesia.